A new copper(I) coordination polymer from 2, 6-bis(1H-benzotriazol-1-ylmethyl)pyridine: Synthesis, characterization, and use as additive in transparent submicron UV filters. Issue 19 (2nd October 2017) - Nuñez-Dallos, Nelson; Lopez-Barbosa, Natalia; Muñoz-Castro, Alvaro; Mac-Leod Carey, Desmond; De Nisi, Assunta; Monari, Magda; Osma, Johann F.; Hurtado, John
Abstract: The use of a new copper(I) coordination polymer (CP) as additive in transparent composite films of 190 nm of thickness for ultraviolet (UV) shielding is presented. The luminescent 1-D Cu(I) CP was easily synthesized through a self-assembly process between Cu(I) iodide and 2, 6-bis(1 H -benzotriazol-1-ylmethyl)pyridine (L). The CP, [Cu2 ( μ − I)2 ( μ − L )2 ] n, was structurally characterized by infrared, UV–visible diffuse reflectance and photoluminescence spectroscopy, elemental and thermogravimetric analyses, single-crystal and powder X-ray diffraction, and relativistic density functional theory calculations. The CP was dispersed and immobilized into a polymeric matrix in the presence of Sudan I, yielding a composite material that exhibits a reduction of 49% of the UV transmittance at 350 nm. Thus, the use of a new Cu(I) CP in polymeric composite films appears as a novel approach toward ultrathin and transparent UV shielding films, which have potential applications as protection layers of paints and coatings that tend to degrade when exposed to UV radiation. Abstract :